The Effect of Principal’s Academic Supervision, Teacher’s Professionalism and Work Environment on Teacher’s Performance - Herliana, Herliana; Kristiawan, Muhammad; Wardiah, Dessy (Yayasan Sembilan Pemuda Indonesia, 2023)
The low performance of teachers is sometimes caused by unsustainable supervision activities carried out in schools, besides that the level of professionalism of teachers in implementing learning is not optimal and the work environment is inadequate. The purpose of this study is to provide an overview of the effect of improving teacher performance through the academic supervision of the school principal, teacher professionalism and the work environment. This research uses quantitative methods. The data collected in this study were obtained through observation, interviews, questionnaires and documentation. The analysis used is multiple linear regression analysis. The results of this study indicate that the influence of the principal’s academic supervision, teacher professionalism, and the work environment jointly affect teacher performance. If academic supervision activities are carried out effectively and continuously, then the teacher’s ability to carry out learning is carried out in a professional manner and the work environment, in addition to meeting standards, also provides positive benefits for teachers, the teacher’s performance will increase.